If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 4t + 13 Reorder the terms: 5 = 13 + 4t Solving 5 = 13 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 5 + -4t = 13 + 4t + -4t Combine like terms: 4t + -4t = 0 5 + -4t = 13 + 0 5 + -4t = 13 Add '-5' to each side of the equation. 5 + -5 + -4t = 13 + -5 Combine like terms: 5 + -5 = 0 0 + -4t = 13 + -5 -4t = 13 + -5 Combine like terms: 13 + -5 = 8 -4t = 8 Divide each side by '-4'. t = -2 Simplifying t = -2
| 3(2n-1)=6n-4 | | x^4+14x^2+48=0 | | X^2-12x+210=0 | | -17(-11+14q)= | | 8.3+8.3+3.8+3.8= | | 3u-4+7=55 | | 0.6(5m+15)=-12 | | 7-3(5-3v)+9v=28 | | 2x-3+8=-27 | | 2x-3+8=27 | | -5y+x=-6 | | -2(n+3)=-12 | | 2y(4x+2y+3)= | | 32.45+1.468x=766.45 | | 2y-10=16 | | -5x+y=-6 | | 9+m*3=2 | | 169x^2-196x^2=0 | | 7x+12=10x+6 | | 4-(x+9)=-x-5 | | w-8+9=-29 | | (1+3b)=-20 | | w-8+9=29 | | X-109.3=184.9 | | 2x-14=x+9 | | 6(5z-8)-4=9+z | | -9+n*4=-7 | | 3x-6=-4 | | -8x=2x+20 | | 7(3x-10)=3(7x-5) | | 0.6x+22=28 | | 5.4X+.4=3.4 |